VERDENSBYER – URBANE FORESTILLINGSVERDENER - Huyssen, Andreas (K&K - Kultur og Klasse, 2010)
The article is an edited version of the article “Introduction: World Cultures, World Cities” in Andreas Huyssen, ed. Other Cities, Other Worlds: Urban Imaginaries in a Globalizing Age. Durham, N.C.: Duke University Press, 2008. The article was translated into Danish by Morten Visby.